THE EFFECT OF FINANCIAL LEVERAGE ON DIVIDEND PAYOUT RATIO: AN APPLIED STUDY FOR INDUSTRIAL COMPANIES LISTED ON THE QATAR STOCK EXCHANGE - Sabir H. Mahmood (Scholar Express Journals, 2023)
The current research aims to uncover the impact of financial leverage on the dividend payout ratio for a number of companies listed on the Qatar Stock Exchange and the extent to which the company's debt affects this ratio. To achieve the research objectives, the necessary data for the study variables were collected. These variables include financial leverage (the independent variable) according to the Debt Ratio (DR) index and the Debt-to-Equity Ratio (DER) index. The data for the Dividend Payout Ratio (DPR) were collected based on the ratio of dividends per share to earnings per share (DPS/EPS). This data was collected from the audited financial statements of industrial companies listed on the Qatar Stock Exchange for the period 2018-2022. The statistical program E-views 13 was used to test the research sample and validate the hypotheses. The research found, through the analysis of the study data, a statistically significant impact of the Debt Ratio (DR) index on the Dividend Payout Ratio (DPR). However, there was no statistically significant impact of the Debt-to-Equity Ratio (DER) index on the dividend payout ratio for the companies in the study sample. The research recommended the use of low-cost external financing tools, especially those compliant with Islamic principles. This is because Islamic external financing tools do not expose the companies in the research sample to the risk of financial distress
Keywords: Financial Leverage; Dividend Payout Ratio; Debt Ratio and the Debt-to-Equity Ratio